Pregnancy outcome among gestational diabetes mellitus patients in a tertiary care centre - M., Jesu Thangam; R., Jameela Ponmalar A.; S., Vishnupriya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Gestational diabetes mellitus poses numerous health problems for both mother and the fetus. Even though there are improved outcomes, complications of gestational diabetes still persists. Objectives of this study was to find out the maternal and perinatal outcomes in gestational diabetes mellitus. Methods: This study was done among pregnant women attending antenatal outpatient department at Sree Mookambika Institute of Medical Sciences, Kulasekharam. oral glucose tolerance test was done at between 24 to 28 weeks and the values more than their cutoff was labelled as gestational diabetes and their outcome was measured as complications during antenatal period, mode of delivery and perinatal outcome in view of neonatal intensive care unit admissions due to hyperbilirubinemia and respiratory distress syndrome. Results: Out of 500 antenatal mothers 65 were found to have gestational diabetes which is approximately 13%. Obstetric outcomes were 10% of them developed pregnancy induced hypertension, 12% of them ended in preterm labour and polyhydramnios in 2%. Delivery by caesarean section and vaginal route is almost similar. Maximum number of neonatal intensive care admissions are due to hyperbilirubinemia followed by respiratory distress. Conclusions: Screening for gestational diabetes and adequate glycemic control is necessary in preventing short term and long-term complications.